Vehicle electrification: technologies, challenges and a global perspective for smart grids - Monteiro, Vítor Duarte Fernandes (2019)
Nowadays, due to economic and climate concerns, the private transportation sector is shifting for the vehicle electrification, mainly supported by electric and hybrid plug-in vehicles. For this new reality, new challenges about operation modes are emerging, demanding a cooperative and dynamic operation with the electrical power grid, guaranteeing a stable integration without omitting the power quality for the grid-side and for the vehicle-side. Besides the operation modes, new attractive and complementary technologies are offered by the vehicle electrification in the context of smart grids, which are valid for both on-board and off-board systems. In this perspective, this book chapter presents a global perspective and deals with challenges for the vehicle electrification, covering the key technologies toward a sustainable future. Among others, the flowing topics are covered: (1) Overview of power electronics structures for battery charging systems, including on-board and off-board systems; (2) State-of-the-art of communication technologies for application in the context of vehicular electrification, smart grids and smart homes; (3) Challenges and opportunities concerning wireless power transfer with bidirectional interface to the electrical grid; (4) Future perspectives about bidirectional power transfer between electric vehicles (vehicle-to-vehicle operation mode); (5) Unified technologies, allowing to combine functionalities of a bidirectional interface with the electrical grid and motor driver based on a single system; and (6) Smart grids and smart homes scenarios and accessible opportunities about operation modes.